A Comparative Study of Trading in Influence in Indonesian and Spanish Corruption Laws - July Esther; Gebi Vani Habeahan; Herlina Manullang (Dinasti Research, 2025)
One of the eleven types of corruption covered by Articles 18 a and b of the United Nations Convention Against Corruption (UNCAC) is trading in influence. Since trading in influence is widespread these days, it needs proper legal control to end this kind of corruption.Therefore, this research will assess the regulatory frameworks for trading in influence Spain and Indonesia, as well as the urgency of regulating trading in influence in accordance with Indonesia's anti-corruption legislation in the future. This study employs a comparative and statutory approach to normative law. According to the findings, there are notable distinctions between the two nations, particularly with regard to the legal framework. Indonesia continues to lag far behind Spain in terms of regulating trading in influence, which calls for a legislative amendment to strengthen the nation's laws.